(REVIEW) Piotr Sztompka, Social capital. Interpersonal space theory, Cracovian publisher Znak, Kraków 2016, pp. 384 - Wojciechowska, Marta Małgorzata (Political Preferences, 2016)
"Social capital. Interpersonal space theory." is prescribed reading for politicians, publicists and responsible citizens, who do not want to become dodgers, but active creators of state community. The reviewed publication is a theoretical study, but the sociologist explains and charts all complicated questions in a way which enables to be understood , even by ordinary people.